2022
DOI: 10.5101/nbe.v14i2.p149-158
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-proliferative Activity of Factory Wastes Nanoparticles against Uterus Cancer Cells: In-vitro Study

Abstract: As a result of increasingly rigorous environmental legislation and industry adoption of waste minimization recommendations, the development of recycling and reuse possibilities for metal-related trash has become increasingly important.Inthis research, calcium oxide and mixture of calcium, iron, and magnesium oxides was extracted from the wastes of cement factories using hydrofluoric acid. As a result, this research provides a comprehensive picture of waste recycling, and reuse throughout extraction and it exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Other related study on ZnO-based materials with excellent antibacterial outcomes was presented in earlier works (Li et al, 2017;Xiang et al, 2017) [46,47]. Furthermore, comparable studies showed that production of ZnO nanoparticles increased antibacterial properties against S. aureus, S. epidermidis, E. coli, and K. pneumoniae bacteria [48].…”
Section: Antibacterial Assaymentioning
confidence: 67%
“…Other related study on ZnO-based materials with excellent antibacterial outcomes was presented in earlier works (Li et al, 2017;Xiang et al, 2017) [46,47]. Furthermore, comparable studies showed that production of ZnO nanoparticles increased antibacterial properties against S. aureus, S. epidermidis, E. coli, and K. pneumoniae bacteria [48].…”
Section: Antibacterial Assaymentioning
confidence: 67%